Medicinal Plants for the Treatment of Mental Diseases in Pregnancy: An In Vitro Safety Assessment - Spiess, Deborah; Winker, Moritz; Chauveau, Antoine; Abegg, Vanessa Fabienne; Potterat, Olivier; Hamburger, Matthias; Gründemann, Carsten; Simões-Wüst, Ana Paula (Planta Medica, 2021)
Pregnancy is a critical period for medical care, during which the well-being of woman and fetus must be considered. This is particularly relevant in managing non-psychotic mental disorders since treatment with central nervous system-active drugs and untreated NMDs may have negative effects. Some well-known herbal preparations (phytopharmaceuticals), including St. Johnʼs wort, California poppy, valerian, lavender, and hops, possess antidepressant, sedative, anxiolytic, or antidepressant properties and could be used to treat mental diseases such as depression, restlessness, and anxiety in pregnancy. Our goal was to assess their safety in vitro, focusing on cytotoxicity, induction of apoptosis, genotoxicity, and effects on metabolic properties and differentiation in cells widely used as a placental cell model (BeWo b30 placenta choriocarcinoma cells). The lavender essential oil was inconspicuous in all experiments and showed no detrimental effects. At low-to-high concentrations, no extract markedly affected the chosen safety parameters. At an artificially high concentration of 100 µg/mL, extracts from St. Johnʼs wort, California poppy, valerian, and hops had minimal cytotoxic effects. None of the extracts resulted in genotoxic effects or altered glucose consumption or lactate production, nor did they induce or inhibit BeWo b30 cell differentiation. This study suggests that all tested preparations from St. Johnʼs wort, California poppy, valerian, lavender, and hops, in concentrations up to 30 µg/mL, do not possess any cytotoxic or genotoxic potential and do not compromise placental cell viability, metabolic activity, and differentiation. Empirical and clinical studies during pregnancy are needed to support these in vitro data.
Keywords: non-psychotic mental disorders; pregnancy; BeWo cell line; toxicity; Hypericum perforatum; Hypericaceae; Eschscholzia californica; Papaveraceae; Valeriana officinalis; Caprifoliaceae; Lavandula angustifolia; Lamiaceae; Humulus lupulus; Cannabaceae